2013
DOI: 10.1097/ncc.0b013e318269040f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Patient-Reported and Clinician-Observed Symptoms in Oncology

Abstract: Symptoms reported by patients themselves provide the necessary and different insight into cancer and its treatment, compared with those observed by clinicians. The use of patient-reported symptoms should be incorporated into routine clinical practice and not just research studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
102
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(122 citation statements)
references
References 44 publications
14
102
2
4
Order By: Relevance
“…It’s a huge issue’ [24]. The disparity between patient-reported and clinician-reported symptoms can negatively impact patient care [25], with one study indicating that healthcare providers underestimated the percentages of moderate or severe symptoms relative to patients’ reports of symptom intensity [26]. …”
Section: Discussionmentioning
confidence: 99%
“…It’s a huge issue’ [24]. The disparity between patient-reported and clinician-reported symptoms can negatively impact patient care [25], with one study indicating that healthcare providers underestimated the percentages of moderate or severe symptoms relative to patients’ reports of symptom intensity [26]. …”
Section: Discussionmentioning
confidence: 99%
“…A systematic review demonstrated that this has been a consistent finding across multiple studies, and concluded that PRO data were essential for the evaluation of symptoms in cancer survivors [3]. Many researchers have hypothesized the reasons behind this discrepancy in physician/patient ratings of symptoms, including poor communication, inadequate physician time spent per patient, and patients' underreport of symptoms to physicians [3].…”
Section: Patient-reported Outcomes To Accurately Capture Treatment-rementioning
confidence: 99%
“…Many researchers have hypothesized the reasons behind this discrepancy in physician/patient ratings of symptoms, including poor communication, inadequate physician time spent per patient, and patients' underreport of symptoms to physicians [3]. Therefore, it is important to incorporate PRO assessment in clinical trials, especially those assessing new treatments.…”
Section: Patient-reported Outcomes To Accurately Capture Treatment-rementioning
confidence: 99%
See 2 more Smart Citations